COMPUTER-GENERATED MUSIC, AUTHORSHIP, AND WORK IDENTITY. - REICHER, Maria Elisabeth (Grazer Philosophische Studien, 2015)
In a paper entitled "Computer Composition and Works of Music: Variation on a Th eme of Ingarden" (1988), Peter Simons explores some ontological problems that ensue from the use of certain forms of composition software, where the final outcome (the score) is the product of random processes within the computer. Such a method of composition raises, among others, the following questions: What kind of work (if any) has been created? Is it a work of music in the first place? Who is the composer/author? Is it the software programmer, the user, the one who selects a particular score for public performance, the computer? What is the relationship of distinct products of the same programme? Are they instances of the same work? In this paper, I shall re-examine these questions.